2015
DOI: 10.2134/agronj14.0399
|View full text |Cite
|
Sign up to set email alerts
|

Trinexapac‐Ethyl Effects on Red Clover Seed Crops in Diverse Production Environments

Abstract: Trinexapac-ethyl (TE) plant growth regulator (PGR) e ects on diploid red clover (Trifolium pratense L.) seed production were investigated in two diverse environments, Canterbury (CA), New Zealand (NZ), and Willamette Valley, Oregon (OR). Five TE rate (250 and 500 g a.i. ha -1 ) and timing [Biologische Bundesanstalt, Bundessortenamt, and CHemische Industrie (BBCH) growth stages 32, 51, 32 + 51] treatments and an untreated control were examined at six on-farm sites in OR and one experimental site in CA in 2011 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…Coupled with the dry and warm conditions in 2015, the reduction in canopy coverage with TE reduced the amount of soil water available for seed filling in the BBCH 32 application of TE. The reduction in height of the crop canopy by TE likely increased transmission of photosynthetic active radiation through the canopy to the soil as reported for TE treatment in red clover seed crops (Anderson et al, 2015). With wet conditions in March and April 2016, no effects of TE on soil water content were detected in early May 2016.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Coupled with the dry and warm conditions in 2015, the reduction in canopy coverage with TE reduced the amount of soil water available for seed filling in the BBCH 32 application of TE. The reduction in height of the crop canopy by TE likely increased transmission of photosynthetic active radiation through the canopy to the soil as reported for TE treatment in red clover seed crops (Anderson et al, 2015). With wet conditions in March and April 2016, no effects of TE on soil water content were detected in early May 2016.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, TE was not observed to cause mortality of stems. However, Anderson et al (2015) reported that stem number in red clover seed crops was increased by applications of TE PGR in New Zealand, whereas Anderson et al (2016) found that TE did not influence stem number in red clover in Oregon.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations